Manajemen Kepala Madrasah Ibtidaiyah Negeri 2 Pekanbaru Dalam Menumbuhkan Pendidikan Karakter Religius Pada Era Digital - Syukri Syukri; Abdul Rouf; Wismanto Wismanto; Khairul Amin; Rafifah Qanita (Departement of Mathematics Education, 2023)
This study aims to find out how the role of school in fostering religious character education in the digital era. The research method used in this study is qualitative. The headmaster of Madrasah Ibtidaiyyah Negeri (MIN 2) Pekanbaru being a main sample in this reseacrh, Data collection techniques using the interview method, obesevation and documentation, Analysis of research data using reduction techniques, triangulation and conclusions from research data. Based on this research, it was concluded that the management of the Head of Madrasah Ibtidaiyah Negeri (MIN) 2 Pekanbaru in fostering religious character education in the digital age by prioritizing the psychological side of students who have implications for behavior, character formation in children is carried out in an effort to create students who have good knowledge and behavior. Character of Madrasah Ibtidaiyah Negeri 2 Pekanbaru Madrasah Students has values ​​that are sourced from Pancasila, Religion, Culture, and the purpose of national education that is honest, tolerance, religious, discipline, cooperation, creative, democracy, independence, national spirit, curiosity, , love of motherland, friendly, communicative, respect for achievement, love of peace, caring for the environment, fond of reading, social care and responsible. Student religiosity is shown by the attitudes or obedience behavior in carrying out the teachings of religion that has been adopted, tolerant of the implementation of religious worship and living in harmony with adherents of other religions. The results from this research showed that the management of Madrasah Ibtidaiyah Negeri (MIN) 2 Pekanbaru in fostering religious character education had been going well by carrying out three principles of management: 1. make a plan what will be carried out, 2. Carrying out what has been planned and 3. evaluation that has been carried out. Information technology helps facilitate all human activities, information search, information delivery and literacy about the addition of knowledge in learning by utilizing technology, so students can learn by utilizing learning resources to the maximum.